Voting power in the EU Council of Ministers and fair decision making in distributive politics - Michel Le Breton; Maria Montero; Vera Zaporozhets (The University of Nottingham, Centre for Decision Research and Experimental Economics (CeDEx), 2011)
We analyze and evaluate the different decision rules describing the Council of Ministers of the EU starting from 1958 up to date. All the existing studies use the Banzhaf index (for binary voting) or the Shapley-Shubik index (for distributive politics). We argue that the nucleolus can be considered an appropriate power measure in distributive situations and an alternative to the Shapley-Shubik index. We then calculate the nucleolus and compare the results of our calculations with the conventional measures. In the second part, we analyze the power of the European citizens as measured by the nucleolus under the egalitarian criterion proposed by Felsenthal and Machover (1998), and characterize the first best situation. Based on these results we propose a methodology for the design of the optimal (fair) decision rules. We perform the optimization exercise for the earlier stages of the EU within a restricted domain of voting rules, and conclude that Germany should receive more than the other three large countries under the optimal voting rule.
Keywords: 330